My Sister and I- The personal account of life with a sibling with Asperger Syndrome - Dimou, Anna (2012)
The purpose of this study is to explore the potential impact of individuals with autism spectrum disorder (ASD) on typically developing siblings. My personal experience with a sister with Asperger syndrome gave me the inspiration for this paper. Through autoethnography I examine this relationship and its effect on me. Within my personal writing-stories I explore my experiences during childhood, adolescence and adulthood with my sister. As well as my thoughts about what I have gained from this experience and the future concerns I have for our relationship. In adittion I discuss my personal experiences in relation to the existing literature. It is clear to see that even in the most functional families with children who are most able to cope with change, having a sibling with an ASD does change normal life occurrences. Families and the individuals that comprise them are both likely to be strengthened and strained as a result of their experience. However the findings in the literature review are mixed and inconsistent, it is never entirely obvious what the impact of disability is likely to have on the relationship between two siblings. A lack of literature on the subject of sibling relationships with an ASD brother or sister in adulthood has been considered an area of concern. Moreover, my own suggestion that is derived from my personal experience could be to explore the effects of an undiagnosed ASD sibling on a typically developing sibling. This paper aims to broaden knowledge and understanding concerning the influence of the ASD individual on the typically development siblings. Personal implications in counselling are also provided.